Photodynamic inactivation of P. aeruginosa strains in order to obtain multistage vaccine - Derkach, S; Martynov, A; Gorodnytska, N; Kutsai, N; Gabisheva, L (Annals of Mechnikov’s Institute, 2020)
Introduction. One of the main pathogens of purulent-inflammatory production, while in the interior remains Pseudomonas aeruginosa. The pathogen has a serogroup landscape, uses a polyresistant of its own and high impurities to disinfectants, asepsis and factors that exist in most. When antibiotics are detected, the effectiveness is insufficient, and trust in the hymen is created on the early and burn surfaces, on catheters, in the formation of a chronic course, which is in overuse of products, and in the absurd, pneumonia, implant differences and problems with prosthetics, which still have to continue. The problem with creating highly effective vaccines against Pseudomonas aeruginosa infection is the availability of vaccine antigens that have shown a protective response independent of serotype and under the type of pathogen, and have been found to be malignant. toxic and non-reactogenic. Look for new products aimed at creating the most modern drugs that are studied in different countries. In Ukraine, there are no diagnostic drugs for the identification of the pathogen and the determination of specific antibodies, and vaccines for the prevention and treatment of Pseudomonas aeruginosa infection Obtaining such drugs of domestic production is promising, relevant and socially and economically justified. Materials and methods. The basis of our proposed method of obtaining a multistage Pseudomonas aeruginosa vaccine is the method of photodynamic disinfection of bacterial cultures. An important feature of this method is its universal effectiveness of inactivation of bacteria and viruses, regardless of serotype, phagovar. For the experiment, 7 regional strains of P. aeruginosa isolated from different habitats stored in purulent-inflammatory sites were studied. As drugs for obtaining samples of the vaccine used a commercial drug - "Pseudomonas aeruginosa bacteriophage" (FDUP "NGO" Microgen ", Perm). As photosensitizers used 1% solution of vikasol (manufactured in Ukraine, "Darnitsa") and 0.1% solution of riboflavin (manufactured in Ukraine, "Darnitsa"). To use the photodynamic effect, we used a photo-polymer stand-alone lamp "Lux" with a powerful luminous flux of 1200 mW / cm2 (power - 90 mW / cm2. Ultraviolet (UV) radiation was used in the laminar box with a bactericidal lamp.. The titer of a mixture of our adapted phages was determined (by the Appelman method), which allowed to determine the dose of phage required for testing the phagolysis technique in experiments with various additives (riboflavin, vikasol). Results and discussion. At a phage titer of 1: 106, complete lysis of test-culture pseudomonads was recorded after 2-18 hours of incubation at a temperature of + 350 C. It should be noted that the growth of single colonies still occurs when sowing from a mixture of pseudomonads + adapted bacteriophages for 3-5 days. . Without irradiation, these substances in any concentrations did not affect the growth of Pseudomonas aeruginosa cultures, while at certain doses (vikasol - 3.5 μg / ml, riboflavin - 0.2 μg / ml) and irradiation parameters there was a decrease or lack of growth of bacterial cultures after sowing from experimental samples. The type and parameters of crop irradiation were determined separately. The irradiation regime was determined experimentally on pure cultures of P. aeruginosa strains taken in different concentrations (from 101 to 109) CFU / ml, at different time intervals (5,0-10, 0-15, 0-20, 0-30, 0 - 40, 0 min), with different concentrations of riboflavin and vikasol, with the addition of bacteriophage samples and without its addition). The optimal parameters for irradiation of the samples are 20 minutes when using UV rays and 30 minutes - when using daylight photopolymer lamp. Significant advantages of one method over another are not presented. To increase the photosensitizing effect, the combined use of viкasol and riboflavin was used. The most promising way to obtain a phagolytic pseudomonas vaccine that is decontaminated and does not contain toxic fractions is the use of specific or adapted to candidate cultures P. aeruginosa bacteriophages, riboflavin and vikasol, followed by irradiation with light or photopopulation. The method of obtaining immunogens developed on the model of P. aeruginosa can be successful for obtaining vaccines from other bacteria - pathogens of purulent-inflammatory diseases (staphylococcus, streptococcus, Escherichia coli, Proteus, etc.) and the design of polyvalent vaccines. DOI: 10.5281/zenodo.3885092